Atmospheric pressure plasma jet treatment of PLA/PAni solutions: Enhanced morphology, improved yield of electrospun nanofibers and concomitant doping behaviour. (2nd December 2022) - Guo, Yongjian; Ghobeira, Rouba; Sun, Zuxin; Shali, Parisa; Morent, Rino; De Geyter, Nathalie
Abstract: To obtain uniform and bead-free nanofibers by means of electrospinning is sometimes very challenging, especially for polymers with low solubility, such as for example the intrinsically conducting polymers (ICPs). Recently, atmospheric pressure plasma jet (APPJ) treatment to pre-electrospinning polymer solutions has been found to effectively enhance the electrospinnability of a single polymer type. Here, such an APPJ treatment has been applied for the first time to a blended polymeric solution consisting of polylactic acid (PLA) and polyaniline emeraldine base (PAni EB) as well as its emeraldine salt (ES) form doped by camphorsulfonic acid (CSA). The plasma-induced physical changes of the solutions including pH, conductivity, viscosity and surface tension have been investigated and correlated with the ensuing physicochemical properties of the electrospun nanofibers. To do so, next to the liquid-based characterizations, the nanofibers have been examined by means of scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), Fourier-transform infrared spectroscopy (FTIR), water contact angle (WCA) goniometry and uniaxial tensile testing. Results revealed that the pre-electrospinning plasma modification step resulted in a remarkably enhanced nanofiber morphology, deposition yield and mechanical performance of the electrospun nanofibers. Moreover, concomitant doping of PAni EB to PAni ES, as an unexpected side behaviour generated during the plasma treatment without the addition of any protonic acid, was found and further carefully investigated using ultraviolet/visible (UV–Vis) spectrometry. The findings obtained in this work thus enlarge the application range of pre-electrospinning APPJ treatment from single to blended polymeric solutions. Moreover, the recent pioneering discovery revealing the pre-electrospinning APPJ treatment role in enhancing electrospinning has surpassed the sole connotation of improved fiber morphology as new interesting effects are discerned in this study: boosted nanofiber deposition yield and doping capabilities. Graphical abstract: Image 1 Highlights: APPJ treatment has been applied for the first time to a blended polymeric solution system. The improved deposition yield is revealed for the first time as an important positive effect of APPJ treatment. Concomitant doping of PAni EB is found as an unexpected side behaviour generated during the APPJ treatment.